Magnesium aluminate spinel and preparation method thereof
By optimizing the solution pH value and process conditions of magnesium aluminum spinel, the high cost and purity problems of magnesium aluminum spinel synthesis in the prior art are solved, and high purity and efficient industrial production are achieved.
Patent Information
- Application Number
- CN202411372259.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-24
AI Technical Summary
The prior art has problems such as high cost, long time, high temperature, low product purity and large impurity content when synthesizing magnesium aluminum spinel, making it difficult to achieve industrial-scale pure magnesium aluminum spinel production.
Use magnesium salt and aluminum salt to dissolve in water at a molar ratio of 1:1.2-2, adjust the pH value of the solution to 9-11, and calcinate after stirring and reaction to obtain magnesium aluminum spinel. By optimizing the precipitant and process conditions, the product is controlled. Purity and crystallinity.
The synthesis of high-purity magnesium aluminum spinel is achieved, which is suitable for large-scale industrial production. The MgO:Al2O3 ratio in the product is close to the theoretical ratio, and the product has a high crystallinity, which reduces raw material consumption and production costs.
Smart Images

Figure BDA0005067889480000041 
Figure BDA0005067889480000051 
Figure BDA0005067889480000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic powder materials, and in particular relates to a magnesium-aluminum spinel and a preparation method thereof. Background Art
[0002] Magnesium aluminum spinel (MgAl2O4) is the most important structure in AB2O4 compounds. Its melting point is 2135℃. It has the advantages of small thermal expansion coefficient, high chemical stability, good thermal shock resistance, excellent mechanical properties at room temperature and high temperature, and good transmittance in ultraviolet, visible light and infrared bands. It is an ideal material for making infrared laser windows, high temperature windows, infrared guided missile domes and high temperature and radiation resistant photographic lenses. Natural magnesium aluminum spinel resources cannot meet the needs of industrial production. The spinels usually used are artificially synthesized. There are three types of artificially synthesized magnesium aluminum spinel: magnesium-rich spinel, aluminum-rich spinel and pure spinel. Magnesium-rich spinel is a composite material of MgO and MgAl2O4, aluminum-rich spinel is a composite material of Al2O3 and MgAl2O4, and pure spinel is pure MgAl2O4. Among them, pure spinel has the strongest acid and alkali corrosion resistance. Traditional solid-phase synthesis technology of magnesium-aluminum spinel mostly uses MgO and Al2O3 as raw materials, with high synthesis temperature (1300℃), long reaction time (about 100h), high production cost, and the introduction of additives leads to low product purity, making it difficult to synthesize pure spinel. At present, the synthesis methods of magnesium-aluminum spinel mainly include solid-phase method, coprecipitation method and sol-gel method. Among them, the coprecipitation method is simple to operate and has high product purity, which is the most likely method to achieve industrialization of pure magnesium-aluminum spinel synthesis.
[0003] Prior art CN1634802A discloses a method for preparing magnesium aluminum spinel nano powder by coprecipitation method. The prepared powder has only magnesium aluminum spinel peak in XRD diffraction pattern. However, the preparation process uses 0.5-0.005 mol / L ammonium bicarbonate aqueous solution as precipitant. On the one hand, more precipitant is consumed to adjust the pH value of the solution, which increases the production cost. On the other hand, it can be seen from the XRD test result of the reaction product that the position of the diffraction peak is offset, and the half-height width of the diffraction peak is large, indicating that the crystallinity of the synthesized magnesium aluminum spinel is not high, and there are many miscellaneous peaks in the XRD spectrum, indicating that the product may contain impurities.
[0004] The prior art CN102139902A discloses a method for synthesizing magnesium-aluminum spinel by low-temperature calcination of chloride-type Mg-Al hydrotalcite. The raw materials are a mixed solution of magnesium chloride and aluminum chloride, sodium chloride is a base liquid, and sodium hydroxide solution is a precipitant. The hydrotalcite is synthesized by a double titration co-precipitation method as a calcination precursor. However, the preparation process needs to be operated under the condition of nitrogen passing at 50-85°C. The operation steps are relatively cumbersome and not conducive to large-scale production.
[0005] Prior art CN102838146A discloses a method for preparing pure spinel phase magnesium aluminum spinel powder with few vacancies. In this method, a mixed solution is prepared according to a molar ratio of MgO:Al2O3 of 3 to 3.8:7, an ammonia solution is added, and the pH value of the solution is adjusted to 8.2 to 8.7. However, at this pH value, the Mg in the solution 2+ It is difficult to precipitate completely, resulting in the consumption of raw materials, and the ratio of MgO:Al2O3 in the dry gel is 1:4.5. The product may contain Al2O3 in addition to MgAl2O4. Many impurity peaks can also be seen from the XRD test results, indicating that the pure magnesium aluminum spinel synthesized by this existing technology has more impurities. Summary of the invention
[0006] The object of the present invention is to provide a high-purity magnesium-aluminum spinel and a preparation method thereof.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for preparing magnesium aluminum spinel comprises the following steps:
[0009] Dissolving magnesium salt and aluminum salt in water according to the molar ratio of Mg ion to Al ion of 1:1.2-2 to prepare a mixed solution; adjusting the pH of the mixed solution to 9-11 with alkali, and then stirring and reacting at 50-80° C. for 0.5-3 hours to obtain a mixture; then separating and grinding the mixture to obtain a precursor; and finally calcining to obtain magnesium aluminum spinel;
[0010] The magnesium salt is MgSO4·7H2O or MgSO4; the aluminum salt is Al2(SO4)3·18H2O.
[0011] In a preferred embodiment, the process of adjusting the pH of the mixed solution with alkali is: dropping the mixed solution and the alkali into an alkaline aqueous solution at the same time, and controlling the pH of the reaction system to be 9-11.
[0012] In a preferred embodiment, the process of adjusting the pH of the mixed solution with alkali is: dropping the alkali into the mixed solution to control the pH of the reaction system to 9-11.
[0013] In a preferred embodiment, the base is one or more of NaOH and KOH.
[0014] In a preferred embodiment, the alkaline aqueous solution is one or more of aqueous solutions of NaOH and KOH.
[0015] In a preferred embodiment, the pH value of the alkaline aqueous solution is 9-11.
[0016] In a preferred embodiment, in the mixed solution, Mg 2+ The concentration is 0.005-1mol / L.
[0017] In a preferred embodiment, in the mixed solution, Al 3+ The concentration is 0.004-1mol / L.
[0018] In a preferred embodiment, the mixed solution is heated by a circulating water bath to maintain the solution temperature at 50-80°C.
[0019] In a preferred embodiment, the reaction is stirred for 0.5-2h.
[0020] In a preferred embodiment, the separation includes filtering, washing and drying the mixture.
[0021] In a preferred embodiment, the filtered material is washed multiple times, and washing is stopped when the washing liquid becomes neutral.
[0022] In a preferred embodiment, the drying is performed by microwave drying.
[0023] In a preferred embodiment, the average particle size of the precursor is 0.01-500 μm.
[0024] The dried precursor is ground to prevent the precursor from agglomerating and affecting the particle size and morphology of the sintered product.
[0025] In a preferred embodiment, the calcination temperature is 800-1200° C. and the calcination time is 2-6 hours.
[0026] Based on the same inventive concept, the present invention also claims to protect the magnesium-aluminum spinel prepared by the preparation method of the magnesium-aluminum spinel.
[0027] Based on the same inventive concept, the present invention also claims to protect the use of the magnesium-aluminum spinel in the preparation of transparent ceramics.
[0028] The invention provides a method for synthesizing and industrializing pure magnesium aluminum spinel. The method is simple to operate and consumes less raw materials. The product XRD spectrum contains only a peak of MgAl2O4. The ratio of MgO:Al2O3 in the product is very close to the theoretical ratio of 28.17:71.73. The product has high purity, a narrow half-height width of the diffraction peak, and high crystallinity.
[0029] In summary, the present invention provides a method for synthesizing and industrializing pure magnesium-aluminum spinel, which is simple to operate, consumes less raw materials, has high product purity, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 The process flow chart of the pure magnesium aluminum spinel synthesis method of the present invention is as follows;
[0032] Figure 2 The XRD diffraction pattern of the sintered product obtained by adjusting the pH value of the mixed salt solution using ammonium bicarbonate in Example 1;
[0033] Figure 3 The XRD diffraction pattern of the sintered product obtained by adjusting the pH value of the mixed salt solution using ammonia water in Example 1;
[0034] Figure 4 The XRD diffraction pattern of the sintered product obtained by adjusting the pH value of the mixed salt solution using NaOH in Example 1;
[0035] Figure 5 The XRD diffraction patterns of the sintered products obtained at different calcination temperatures described in Example 2;
[0036] Figure 6 The XRD diffraction pattern of the sintered product obtained by synchronously dropping the alkali solution and the mixed salt solution in Example 4; wherein, Figure 6 a is the XRD diffraction pattern of the sintered product at pH = 9; Figure 6 b is the XRD diffraction pattern of the sintered product at pH = 10; Figure 6 c = XRD diffraction pattern of the sintered product at pH 11;
[0037] Figure 7 This is the XRD diffraction pattern of the sintered product obtained when the aging time is set to 2h in Example 5. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0039] Example 1
[0040] Synthesis of different magnesium-aluminum spinels by optimizing the precipitant
[0041] The steps of synthesizing magnesium aluminum spinel are as follows: 1) MgSO4·7H2O and Al2(SO4)3·18H2O are added to a reactor in a molar ratio of n(MgSO4·7H2O):n[Al2(SO4)3·18H2O]=1:1, and ultrapure water is added to the reactor to adjust the concentration of the mixed solution to 0.5 mol / L, so that n(MgSO4·7H2O) is added to the reactor in a molar ratio of n(MgSO4·7H2O):n[Al2(SO4)3·18H2O]=1:1. 2+ ):n(Al 3+ )=1:2, the reactor is equipped with a stirring paddle, which is rotated and stirred for 10-30 minutes to fully dissolve the raw materials;
[0042] 2) adding a precipitant (sodium hydroxide, ammonium bicarbonate or ammonia water) or an alkaline solution to the mixed solution at a constant rate, adjusting the pH value of the solution, stirring with a stirring paddle continuously, so that the pH value of the solution is stabilized between 9 and 11, heating the mixed solution in the reactor by a circulating water bath, maintaining the solution temperature at 80° C., and aging for 0.5 h;
[0043] 3) The reacted solution is extracted from the bottom of the reactor and transported to a filter press for water washing and preliminary drying. The pH value of the precursor washing solution is tested and the washing is continued until the precursor washing solution is neutral;
[0044] 4) The precursor is further dried using a microwave drying device, and the precursor is in small blocks;
[0045] 5) The dried precursor is ball-milled to prevent the precursor from agglomerating and affecting the particle size and morphology of the sintered product. The average particle size of the ground precursor is 40 μm. The obtained precursor powder is placed in a sagger and calcined at a calcination temperature of 900°C and a holding time of 12 hours to obtain a compound powder containing a MgAl2O4 phase.
[0046] After mixing Al salt and Mg salt in a stoichiometric ratio, the pH value was adjusted using NaOH, ammonia water, and ammonium bicarbonate. The preliminary test results showed that when the pH of the mixed salt solution was 8, there was little precipitation in the solution, so the pH value was adjusted to 9, 10, 11, and 12, respectively. The XRF test results of the products synthesized using different precipitants are shown in Table 1 below, and the XRD test results are shown in Table 1 below. Figure 2 , Figure 3 , Figure 4 shown.
[0047] Table 1 XRF test results of spinel synthesized by different precipitants
[0048]
[0049]
[0050] As can be seen from the table, as the pH value of the solution increases, the MgO:Al2O3 ratio is getting closer to the theoretical ratio of 28.17:71.73. This is because the OH in the solution - Increased concentration of Mg 2+ The sedimentation is more complete. Figure 2 , Figure 3 , Figure 4 It can be seen that when the pH value is between 9 and 11, the XRD diffraction pattern of the synthesized product only has the peak of MgAl2O4, but the XRF test results show that the MgO:Al2O3 ratio in the product is less than the theoretical ratio, which indicates that in addition to MgAl2O4, a part of Al2O3 is dissolved in MgAl2O4. When pH = 12, in addition to the peak of MgAl2O4, the peak of MgO is also detected in the XRD diffraction pattern of the product, and the XRF test results show that MgO:Al2O3 exceeds the theoretical ratio, which indicates that in addition to MgAl2O4, MgO is also generated in the product, and MgO is not completely dissolved in MgAl2O4. This is because too high a pH value causes Al 3+ The Al(OH)3 produced by precipitation and the excess OH - Combined to form AlO 2- , AlO 2- It redissolves into the solution, causing Al 3+ Adjusting the pH value to 12 will not only produce MgO impurities, but also cause the dissolution of the precipitate, resulting in the consumption of raw materials. Therefore, in subsequent studies, the pH value of the mixed salt solution is adjusted to 9-11, preferably, the pH value is adjusted to 11.
[0051] By comparing the MgO:Al2O3 of the products synthesized by the three precipitants, it can be found that when the solution is adjusted to the same pH value, the MgO:Al2O3 of the product obtained by adjusting the pH value using NaOH is closer to the theoretical ratio. In addition, NaOH is a strong base, and compared with the other two precipitants, the consumption of NaOH is smaller, which is suitable for industrial production. Therefore, NaOH is selected as the precipitant.
[0052] Example 2
[0053] The operation steps are the same as those in Example 1, the precipitant is sodium hydroxide, and the pH value is 11. The difference is that the precursor powder obtained in step 5) is placed in a sagger, and the heat treatment process is 600℃ / 2h, 800℃ / 2h, 1000℃ / 2h, 1200℃ / 2h, 1400℃ / 2h, and the heating rate is 3℃ / min. Other operations are the same as those in Example 1. The XRD test results of the five sintered products are as follows: Figure 5 shown.
[0054] from Figure 5It can be seen that when the calcination temperature is 600℃, the diffraction peak of the sintered product is not obvious, indicating that MgAl2O4 is not formed. When the calcination temperature is 800℃, an obvious MgAl2O4 diffraction peak can be observed. When the calcination temperature increases from 800℃ to 1000℃ and 1200℃, the diffraction peak gradually refines and the peak intensity gradually increases, indicating that the MgAl2O4 crystallite gradually grows. When the calcination temperature increases from 1200℃ to 1400℃, there is no obvious change in the diffraction peak intensity, indicating that the precursor has completely formed MgAl2O4 at 1200℃, so the calcination temperature is 800-1200℃.
[0055] Example 3
[0056] Optimization of the amount of aluminum salt added to synthesize magnesium-aluminum spinels with different compositions
[0057] The product synthesized in Example 1 contains not only MgAl2O4, but also part of MgO dissolved in MgAl2O4. Therefore, MgAl2O4 is synthesized by changing the concentration of aluminum salt and then changing the amount of aluminum salt added. The operation steps are the same as those in Example 1, the precipitant is sodium hydroxide, and the pH value is 11. The difference is that 0.5 mol / L MgSO4 solution is mixed with 0.4 mol / L, 0.3 mol / L, and 0.2 mol / L Al2(SO4)3·18H2O solutions, respectively. The other operations are the same as those in Example 1. The XRF test results of the synthesized products are shown in Table 2 below.
[0058] Table 2 XRF test results of products synthesized with different aluminum salt concentrations
[0059]
[0060] From the XRF test results, it can be seen that when the aluminum salt concentration is 0.6 mol / L, the MgO:Al2O3 of the product is much smaller than the theoretical ratio of 28.17:71.73, indicating that the Al in the solution 3+ Excessive, the concentration of aluminum salt needs to be reduced. When the aluminum salt concentration is 0.5mol / L, the MgO:Al2O3 of the product is less than the theoretical ratio, indicating that the aluminum salt concentration is still high at this time, and the aluminum salt concentration needs to be appropriately reduced. When the aluminum salt concentration is 0.3mol / L and 0.2mol / L, the MgO:Al2O3 of the product is greater than the theoretical ratio, indicating that the magnesium salt is excessive at this time, the aluminum salt content is low, and the aluminum salt concentration needs to be increased appropriately. When the aluminum salt concentration is 0.4mol / L, MgO:Al2O3 is close to the theoretical ratio, and magnesium-aluminum spinel is synthesized. Therefore, under the condition that other experimental conditions remain unchanged, the suitable concentration ratio of magnesium salt to aluminum salt is 1:0.6~1:1.0, preferably, the concentration ratio of magnesium salt to aluminum salt is 1:0.8.
[0061] Example 4
[0062] Optimize the dosing sequence
[0063] The operation steps are the same as those in Example 1, except that the Al salt solution and the Mg salt solution are not mixed to obtain a mixed solution, and then NaOH is added dropwise to the mixed solution, the pH value is adjusted to a set value, and a water bath is heated. In the process of adding NaOH dropwise to the mixed solution, the reaction may have already started, and the reaction is still ongoing before the pH value of the solution reaches the set value. During this period of time, the solution does not reach the set pH value, which may affect the Mg 2+ and Al 3+ The precipitation is affected. Therefore, instead, Al salt (0.5 mol / L) and Mg salt (0.5 mol / L) in a stoichiometric ratio are mixed and loaded into a burette, and the mixed salt solution is added dropwise to an aqueous solution with a set pH value (NaOH is added to the aqueous solution to adjust the pH value to the set value). During the addition of the mixed salt solution, NaOH solution is added dropwise simultaneously to keep the pH value of the aqueous solution at the set value, thereby eliminating the effect of the pH adjustment process on the reaction. After all the mixed salt solution has been added dropwise, the solution is placed in a water bath and heated in a water bath at 65°C, centrifuged 3 to 4 times, and then washed with water and filtered to obtain a precursor. The XRF test results of the obtained sintered product are shown in Table 3 below. SiO2 standard substance is added to the sintered product to which the mixed salt solution and alkali solution are added dropwise simultaneously for semi-quantitative analysis. The obtained XRD diffraction pattern is shown in the following Table 3. Figure 6 shown.
[0064] Table 3 XRF test results of products synthesized by synchronously dropping mixed salt solution and alkali solution at different pH values
[0065]
[0066] Under the experimental condition of simultaneous addition of mixed salt solution and alkali solution, it can be seen from the XRF and XRD test results of the sintered products that as the pH value increases, the proportion of MgO in the product gradually increases, and the proportion of Al2O3 gradually decreases. Figure 6 As shown in a, when pH = 9, the MgO content in the product is only 21.03wt%, MgO:Al2O3 = 21.17:78.83, which is far lower than the theoretical level of 28.17:71.73, indicating that at pH = 9, the solution has a large amount of Mg 2+ It was not converted into precipitation. It can also be seen from the XRD spectrum that there is an Al2O3 peak in the product, indicating that there is an excess of Al2O3 in the product. Through the semi-quantitative analysis of XRD, it was found that the content of MgAl2O4 in the product was 96wt% and the content of Al2O3 was 4wt%; Figure 6As shown in Fig. b, when pH = 10, the XRF test results show that the product has MgO:Al2O3 = 23.70:76.30, which is lower than the theoretical level, but no Al2O3 peak is found in the XRD test results, indicating that the excess Al2O3 is dissolved in MgAl2O4, and the obtained product is an aluminum-rich spinel; Figure 6 As shown in Figure c, when pH = 11, the MgO:Al2O3 in the product is close to the theoretical ratio of 26.08:73.92, and there are only MgAl2O4 peaks and peaks of added Si powder in the XRD spectrum. It can be inferred that the simultaneous dropwise addition of the mixed salt solution and the alkali solution is beneficial to the synthesis of pure aluminum magnesium spinel.
[0067] Example 5
[0068] Optimize aging time
[0069] The operation steps are the same as those in Example 1, except that the aging time is adjusted to 0.5 h, 2 h, 3 h, and 4 h, respectively. After the mixed salt solution is adjusted to the set pH value, it is placed in a water bath for water bath heating, i.e., the aging process. During the aging process, the Al in the solution 3+ and Mg 2+ With OH - Combined to form a precipitate, the aging process provides kinetic conditions (temperature, time) for the chemical reaction. From the perspective of chemical reaction kinetics, extending the aging time will increase the Mg content in the solution. 2+ The XRF test results of the sintered products obtained at different aging times are shown in Table 4. When the aging time is 2h, SiO2 is added to the sintered product for semi-quantitative analysis, and the XRD diffraction pattern obtained is as follows: Figure 7 shown.
[0070] Table 4 XRF test results of synthetic spinel with different aging time
[0071]
[0072] From the XRF and XRD test results, it can be seen that when the aging time is 2h, the MgO:Al2O3 in the product is 28.01:71.99, which is very close to the theoretical content ratio of aluminum-magnesium spinel 28.17:71.73, and there are only peaks of MgAl2O4 crystal phase and added Si powder in the XRD spectrum. Therefore, it can be judged that pure aluminum-magnesium spinel was successfully synthesized. When the aging time is 3h and 4h, the MgO:Al2O3 of the product is almost unchanged, so the aging time is set to 2h to make the Mg in the solution 2+ and Al 3+ Complete precipitation.
[0073] Comparative Example 1
[0074] According to Example 2 of the prior art CN 108264342 A, magnesium aluminum spinel powder is prepared, comprising the following steps:
[0075] 1) Al2(SO4)3 and Mg(NO3)2 are dissolved in water at a molar ratio of Al2O3:MgO of 1:1, and the mass concentration of Mg(NO3)2 is 80g / L after the dissolution is completed. The mixture is mixed evenly and dried at 600°C to obtain a precursor;
[0076] 2) The precursor is calcined at 850° C. for 3 h to obtain high-purity magnesium aluminum spinel nanopowder.
[0077] After testing, the material purity of Comparative Example 1 is 99.3%, and contains obvious impurities with a particle size range of 20-80 nm.
[0078] Comparative Example 2
[0079] According to the prior art CN 112010331 A, Example 1 is used to prepare magnesium-aluminum spinel powder, which comprises the following steps:
[0080] 1. Mixing: Add 20L of water to a 50L reactor, and heat the water in the reactor to 40°C. Pour 3Kg of magnesium nitrate hexahydrate and 8.8Kg of aluminum nitrate nonahydrate into the water in the reactor, wherein the molar ratio of Mg ion to Al ion is about 1:2. Stir with a stirring paddle to fully dissolve the magnesium nitrate hexahydrate and aluminum nitrate nonahydrate in the water at a stirring speed of 150r / min to obtain a mixed solution.
[0081] 2. Add alkali reaction: weigh about 3.7 kg of NaOH and prepare it into a 20 mol / L NaOH solution. The Mg ions in the magnesium inorganic salt and the OH in the alkali solution - The molar ratio is 1:8. After cooling to below 40°C, it is placed in the titration device of the reactor and gradually dripped into the above-mentioned mixed solution. The dripping rate is controlled to 80mL / min. The dripping is completed in about 1h. After the dripping is completed, the pH of the sol is 8-9; then ammonia water is dripped into the sol to adjust its pH to 11-12. The ammonia water dripping rate is 80mL / min. After the dripping is completed, the reaction is continued to stir for 1h. After the reaction is completed, a colloid is obtained.
[0082] 3. Gradual filtration: The colloid after the reaction in step 2 is first filtered through a 10μm filter bag at a filtration rate of 15L / h, then filtered through a 3μm filter bag at a filtration rate of 8L / h, and filtered repeatedly three times with water to obtain a filtered colloid.
[0083] 4. Cleaning and impurity removal: put the colloid filtered in step 3 into a 3μm filter bag, place an ultrasonic transmitter in the filter bag, set running water outside the filter bag, the water inlet rate into the filter bag is 2L / h, the water outlet rate is 2L / h, after 5 hours of cleaning, the conductivity of the filtrate is close to that of distilled water. Through this method, the residual impurities such as charged ions soluble in water can be cleaned to obtain the colloid after dialysis and desalination.
[0084] 5. Drying: The colloid obtained in step 4 after dialysis and desalination is placed in a blast oven for drying at a temperature of 80° C. The dried colloid is ground into fine powder to obtain a ground precursor.
[0085] 6. Calcination: Calcinate the ground precursor obtained in step 5 at a temperature of 1200° C. for 2 h, with a heating rate of 5° C. / min and a cooling rate of 5° C. / min to obtain magnesia-alumina spinel powder.
[0086] 7. Grinding: The calcined magnesium aluminum spinel powder is ground into submicron fine particle powder by Raymond mill. The yield of magnesium aluminum spinel is 1.2 kg. However, the obtained magnesium aluminum spinel contains obvious impurities as identified by XRD pattern.
[0087] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing magnesium aluminum spinel, characterized in that: The following steps are involved: Dissolving magnesium salt and aluminum salt in water according to the molar ratio of Mg ion to Al ion of 1:1.2-2 to prepare a mixed solution; adjusting the pH of the mixed solution to 9-11 with alkali, and then stirring and reacting at 50-80° C. for 0.5-3 hours to obtain a mixture; then separating and grinding the mixture to obtain a precursor; and finally calcining to obtain magnesium aluminum spinel; The magnesium salt is MgSO4·7H2O or MgSO4; the aluminum salt is Al2(SO4)3·18H2O.
2. The preparation method according to claim 1, characterized in that: The process of adjusting the pH of the mixed solution by using alkali is as follows: the mixed solution and the alkali are simultaneously dripped into the alkaline aqueous solution, and the pH of the reaction system is controlled to be 9-11.
3. The preparation method according to claim 1, characterized in that: The process of using alkali to adjust the pH of the mixed solution is: dropping the alkali into the mixed solution to control the pH of the reaction system to 9-11.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The alkali is one or both of NaOH and KOH; the alkaline aqueous solution is one or both of aqueous solutions of NaOH and KOH; The pH value of the alkaline aqueous solution is 9-11.
5. The preparation method according to claim 1, characterized in that: In the mixed solution, Mg 2+ The concentration of Al is 0.005-1mol / L; 3+ The concentration is 0.004-1mol / L.
6. The preparation method according to claim 1, characterized in that: The stirring reaction time is 0.5-2h.
7. The preparation method according to claim 1, characterized in that: The average particle size of the precursor is 0.01-500 μm.
8. The preparation method according to any one of claims 1-3 or 4-7, characterized in that: The calcination temperature is 800-1200° C. and the calcination time is 2-6 hours.
9. The magnesium-aluminum spinel prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the magnesium aluminum spinel according to claim 9 in the preparation of transparent ceramics.
